2021
DOI: 10.1038/s41598-021-82905-x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional response to the host cell environment of a multidrug-resistant Mycobacterium tuberculosis clonal outbreak Beijing strain reveals its pathogenic features

Abstract: Tuberculosis is a global public health problem with emergence of multidrug-resistant infections. Previous epidemiological studies of tuberculosis in Thailand have identified a clonal outbreak multidrug-resistant strain of Mycobacterium tuberculosis in the Kanchanaburi province, designated “MKR superspreader”, and this particular strain later was found to also spread to other regions. In this study, we elucidated its biology through RNA-Seq analyses and identified a set of genes involved in cholesterol degradat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 59 publications
3
22
0
Order By: Relevance
“…A recent study also found that the "MKR superspreader" strain of Mtb, an emergent multidrug-resistant strain of the modern Beijing lineage, displayed enhanced upregulation of cholesterol utilization genes during macrophage infection relative to the H37Rv reference strain (13). V-59 was used to show that activating Rv1625c to inhibit cholesterol utilization in the MKR strain selectively reduced intracellular survival of the bacteria in infected macrophages (13). This suggests that efficacy of Rv1625c agonists may be potentiated by cholesterol-related metabolic adaptations that are especially crucial to the intracellular survival of at least one multi-drug resistant strain of Mtb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study also found that the "MKR superspreader" strain of Mtb, an emergent multidrug-resistant strain of the modern Beijing lineage, displayed enhanced upregulation of cholesterol utilization genes during macrophage infection relative to the H37Rv reference strain (13). V-59 was used to show that activating Rv1625c to inhibit cholesterol utilization in the MKR strain selectively reduced intracellular survival of the bacteria in infected macrophages (13). This suggests that efficacy of Rv1625c agonists may be potentiated by cholesterol-related metabolic adaptations that are especially crucial to the intracellular survival of at least one multi-drug resistant strain of Mtb.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, Mtb requires cholesterol metabolism to maintain optimal chronic lung infection (7)(8)(9)(10)(11) and cholesterol utilization was recently found to belong to a set of "core virulence functions" required for Mtb survival in vivo across a genetically diverse panel of mice (12). Furthermore, it was recently demonstrated that a multi-drug resistant strain of Mtb is more dependent on cholesterol for growth than an H37Rv reference strain (13). Thus, the cholesterol metabolic pathway in Mtb represents a novel, genetically validated target for drug discovery.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of next-generation sequencing (NGS) facilitates the genomic and transcriptomic research of mycobacteria. The genomic or transcriptomic analysis focuses on the variation of genomic features, such as gene expression level, DNA sequencing or regulatory elements annotation, which enables the identification of essential genetic or regulatory targets under certain conditions (16)(17)(18). Resistance mutation of mycobacterium to drugs can be detected by genomic analysis of clinical isolates (19).…”
Section: Genomics Transcriptomics and Proteomicsmentioning
confidence: 99%
“…RNAseq and methylome analysis of different clades of Mtb complex detected differential gene expression involved in host interaction and metabolism, which is further linked to the varied phenotypes and host susceptibility between the Mtb complex ( 21 ). RNAseq has been used to identify the relevant virulent genes in clinical Mtb strains such as the MKR mutant ( 17 ). Genes involved in cholesterol degradation as well as ESX-1 secretion system were up-regulated in the MDK strain but not in Mtb H37Rv ( 17 ).…”
Section: Genomics Transcriptomics and Proteomicsmentioning
confidence: 99%
See 1 more Smart Citation